The Use of Peripheral Blood-Derived Stem Cells for Cartilage Repair and Regeneration In Vivo: A Review - Chen, You-Rong; Yan, Xin; Yuan, Fu-Zhen; Ye, Jing; Xu, Bing-Bing; Zhou, Zhu-Xing; Mao, Zi-Mu; Guan, Jian; Song, Yi-Fan; Sun, Ze-Wen; Wang, Xin-Jie; Chen, Ze-Yi; et al. (Frontiers in Pharmacology, 2020)
Background: Peripheral blood (PB) is a potential source of chondrogenic progenitor cells that can be used for cartilage repair and regeneration. However, the cell types, isolation and implantation methods, seeding dosage, ultimate therapeutic effect and in vivo safety remain unclear. Methods: PubMed, Embase, and the Web of Science databases were systematically searched for relevant reports published from January 1990 to December 2019. Original articles that used PB as a source of stem cells to repair cartilage in vivo were selected for analysis. Results: A total of 18 studies were included. Eight human studies used autologous nonculture-expanded PB-derived stem cells (PBSCs) as seed cells with the blood cell separation isolation method, and 10 animal studies used autologous, allogenic or xenogeneic culture-expanded PB-derived mesenchymal stem cells (PB-MSCs) or nonculture-expanded PBSCs as seed cells. Four human and 3 animal studies surgically implanted cells, while the remaining studies implanted cells by single or repeated intra-articular injections. 121 of 130 patients (in 8 human clinical studies), and 230 of 278 animals (in 6 veterinary clinical studies) using PBSCs for cartilage repair achieved significant clinical improvement. All reviewed articles indicated that using PB as a source of seed cells enhances cartilage repair in vivo without serious adverse events. Conclusion: Autologous nonculture-expanded PBSCs are currently the most commonly used cells among all stem cell types derived from PB. Allogeneic, autologous and xenogeneic PB-MSCs are more widely used in animal studies and are potential seed cell types for future applications. Improving the mobilization and purification technology, and shortening the culture cycle of culture-expanded PB-MSCs will obviously promote the researchers' interest. The use of PBSCs for cartilage repair and regeneration in vivo are safe. PBSCs considerably warrant further investigations due to their superiority and safety in clinical settings and positive effects despite limited evidence in humans.